Physiochemical Properties of Soil from Waste Dumpsites within Choba, Alakahia and Rumuosi Communities in Akpor, Rivers State, Nigeria - N. Amadi; M. Yabrade; O. H. Nsan-Nicholas; V. L. Gbosidom (Journal of Applied Sciences and Environmental Management, 2024)
The objective of this paper was to evaluate the physicochemical properties of soil from solid waste dumpsites within Choba, Alakahia and Rumuosi in Akpor, Rivers State, Nigeria using a standard analytical methods. Date obtained show that the values of pH; Cation Exchange Capacity (meq/100g); Phosphorus (mg/kg); Potassium (mg/kg) and Nitrogen (%) were 6.5; 2.8; 1.6; and 0.4 in Choba; 6.7; 2.4; 2.5; 9 and 0.48 in Alakahia, 8.2; 1.9; 3.4; 31.0 and 0.7 in Rumuosi respectively. Furthermore; Results showed that there was an increase in the pH, potassium, phosphorus, nitrogen content value at each dumpsite than their corresponding control. Potassium level was higher at Rumuosi dumpsites than other sites. The mean soil porosity indicated higher porosity in the control sites (0.2 ±0.001 – 0.32 ±0.0012). The soil particle size distribution indicated an average of 82% sand, 8.2% clay and 3% silt for dumpsite and 75% sand, 8.5% clay and 5% silt for control site. Indeed, based on the study findings, it can be concluded that solid waste dumps alter the soil nutrient contents with no-impact on the physical characteristics of the soil, such as its particle size distribution and texture. Therefore, continued monitoring and management of solid waste dumps are necessary to ensure the long-term health and sustainability of soils and surrounding ecosystems.